Legal Framework Incentives for Entrepreneurship - Taneski, Ana; Koritnik, Boštjan (Izboljševanje podjetniške izkušnje s pomočjo podpornega okolja v Ljubljanski urbani regiji, 2025)
This chapter examines the legal framework for entrepreneurship incentives, which include financial and non-financial support offered by public and private actors to future entrepreneurs. The focus is on the legal assessment of these relationships, particularly regarding the allocation of public funds. Literature on entrepreneurial support identifies also non-financial assistance, such as support environments that include future entrepreneurs and are established in Slovenia by regional development agencies. To better understand the practical implementation, regulation of contractual relations, and mechanisms for fund monitoring, we conducted an interview with Dejan Marinčič, advisor to the Director for Entrepreneurship and Innovation at the Regional Development Agency of the Ljubljana Urban Region. Our findings show that the analyzed contractual relationships combine elements of public law, labor law, and the law of obligations. They are structured to implement public interest measures aimed at supporting entrepreneurship. While the autonomy of the contracting parties is limited due to pre-determined legal provisions, this ensures legal certainty, transparency, and the pursuit of broader social objectives. These include the promotion of entrepreneurship and the responsible use of public resources. The regulation of such relationships is thus both a legal necessity and a tool for effectively achieving the intended economic and social impact.